(untitled) (Damascus University Journal of agriculture sciences, 2023)
Experiment carried out at the Abo Jarash Farm, Faculty of Agriculture, Damascus University in 2020 according to Randomized Block Design Complete, 20 basins were planted with sunflower seeds and distributed to 5 water treatments at a rate of four replications per treatment: Control T1 (100% freshwater) Fresh), T2 (75% freshwater + 25% wastewater), T3 (50% freshwater + 50% wastewater), T4 (25% freshwater + 75% wastewater), T5 (100% wastewater). The water was analyzed before irrigation and filtrate of water was taken after watering in the flowering and maturation stages of the plant and comparing them with the Syrian standard Treated wastewater for irrigation purposes No. (2752) for 2008. The chemical parameters were estimated in water filtration (Pb, Ni, Cr, Na+, K+, EC), The results of water filtration analysis showed a decrease in (Pb, Ni, Cr) concentrations in the water filtrate when moving from the flowering stage to the maturation stage. Both treatments (T3, T2) in the seed ripening phase became suitable for irrigation and the value of (Pb, Ni) for the treatment T2 (0.76, 0.9) mg/l, and for treatment T3 (1.133, 3.00) mg/l. While the concentrations of (Na+, K+, • EC) increased in the water filtrate when moving from flower to maturity in all treatments as a result of competition between them and heavy metals for absorption sites in the plant. Treatment T5 had the highest concentrations (Na+, K+, EC) were recorded (1600, 92.01, 107.14). The samples of sunflower leaves were analyzed in the flowering and maturity phases and the chemical indicators were estimated (Pb, Ni, Cr, Na+, K+),The results showed the ability of Helianthus annuus leaves to absorb (Pb, Ni, Cr), where the highest value of nickel was in the treatment T5 in the maturation stage (0.81) mg/l, while the concentrations of sodium and potassium decreased significantly with the increase in the concentrations of heavy metals in the leaves of the plant.